Volume 2: Symposia, Parts A, B, and C 2003
DOI: 10.1115/fedsm2003-45002
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Chain-Reaction Behavior at Bubble Collapse Using Ultra High Speed Video Camera

Abstract: Collapsing behavior of cavitation bubbles is a very short phenomenon. In this study a new ultra-high-speed video camera with the maximum frame speed of 106 fps is used to observe the detailed aspects of three cavitation patterns such as separated vortex cavitation in a convergent-divergent channel, Karman-vortex-like cavitation in the wake flow of a circular cylinder and vibratory cavitation in an ultrasonic vibratory apparatus. For a convergent-divergent channel, the re-entrant motion within the separation zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
2
1
0
1
Order By: Relevance
“…Through the existing results (see, the previous papers [8][9][10][11][12]) in addition to the present result shown in the preceding chapter, a periodic shedding and reentrant mechanism of cloud cavitation can be proposed as schematically shown in Fig. 6.…”
Section: Periodic Process In Cloud Cavitationsupporting
confidence: 64%
See 1 more Smart Citation
“…Through the existing results (see, the previous papers [8][9][10][11][12]) in addition to the present result shown in the preceding chapter, a periodic shedding and reentrant mechanism of cloud cavitation can be proposed as schematically shown in Fig. 6.…”
Section: Periodic Process In Cloud Cavitationsupporting
confidence: 64%
“…Through a high-speed video observation and an image analysis it is pointed out that the pressure wave due to the collapse of cloud shed downstream can induce the reentrant motion. A periodic structure of cloud cavitation is summarized using the present result together with previous results due to the authors [8][9][10][11][12]. As a result the whole process of cloud cavitation is explained in which cavitation clouds are shed periodically.…”
Section: Introductionsupporting
confidence: 59%
“…As a result, it is observed that there is a shorter periodic behavior of cavity length accompanied with a shrinking, growing and shedding motion of clouds which is caused due to the cavitation cloud unsteadiness by nature [16,17], which is not affected by upstream pressure fluctuation due to the plunger pump. Here, the Strouhal number based on cavity length l (St = nl/u) is estimated to be about 0.28, where u is mean flow velocity at the nozzle throat and n is frequency of cavity length oscillation.…”
Section: Figure 9 Relation Between Frequency Of Pump Pulsation and Cmentioning
confidence: 99%
“…キャビテーション現象において,キャビテーションクラウドの挙動は個々のキャビテーション気泡の動的挙動 と同様に重要な働きを果たす.衝撃性の強いキャビテーションクラウドの代表的な例は,水中での高速ウォータ ジェットの剪断層に生じる渦キャビテーションによって形成される微細気泡群である.これまでの多くの研究 (1) ~(6) によれば水中でのキャビテーティングウォータジェット(Cav-Jet と略する)は周期的に不連続なキャビテー ションクラウドを形成し,そのクラウド崩壊時に強い衝撃作用を呈することが知られている.この衝撃作用は産 業的に注目され,洗浄,切断・掘削,ピーニングなどに利用されている. キャビテーションクラウドにおける強い衝撃作用の機構については, 例えば Reisman ら (7) は急速なクラウド 崩壊を引き起こす収縮タイプ発生の条件を満たす時に,強い圧力波あるいは衝撃波が形成されることを理論的に 示している.著者らの既存の実験的研究 (8) (9) によれば,Cav-Jet が固体壁面に衝突するときキャビテーションク キャビテーションクラウドにおける圧力波伝播とその画像解析 © 2011 The Japan Society of Mechanical Engineers ラウドは急速に変形し,その崩壊時に強い衝撃作用を引き起こすことが示されている.つまり,キャビテーショ ンクラウドの崩壊がクラウドあるいは気泡の連続的な崩壊 (10) を引き起こし,衝撃性圧力パルスから成る複雑な 流れ場を形成することが指摘されている. 本研究の最終的な目的は,産業的にも学術的な観点からも重要である衝撃性キャビテーションクラウドを作り 出す基本的な機構を明らかにすることである.キャビテーションクラウドを有する周期的な非定常ウォータジェ ットが高速ビデオカメラを使用して高速度観察され,フレーム間差分法 (11) から圧力波の伝播速度の概略値を与えることができる.例えば右側方向への伝播速度は約170m/sと評価できる. この値よりクラウド状態における圧力波伝播速度の低下 (12) が確認できる. また,図 6(a)中の点 R 0 (z/d=7.8)および点 R 1 (z/d=14.6)はそれぞれ図 5(a)に示されるハイドロフォン…”
Section: 緒 言unclassified